Factors Identification of Undergraduate’s Academic Career Development Readiness - Sapkota, Bachchu Ram (Khwopa Journal, 2025)
Personal traits and environmental circumstances of pupils are important influential factors for their academic career growth. The primary goal of this study is to find out career readiness indicators of undergraduate students and put them into the test and validate a reflective measurement model of students' academic career readiness. To achieve the research aims, a descriptive analytical study is employed to determine the students' learning activities and practices in connection to academic career readiness. A structured questionnaire was distributed to the respondents (100 students from the grade XI/XII management stream), and information from 97 legitimate respondents was gathered and evaluated. The measurement model assessment and hypothesis test results were analyzed and interpreted. The study revealed a valid model of an unobserved construct with seven observed elements in which study sincerity, health consciousness, free form mental stress, sufficient time for study, self-decision freedom, family support and wish to work in native land were approved as reliable and valid components of undergraduate students’ academic career readiness in the institution. This study model has the potential to solve the difficulties in institutions in improving educational performance, and it provides a way to build a valid model for further research